Exploring the vaccine-induced immunity against severe acute respiratory syndrome coronavirus 2 in healthcare workers - Yong Kwan Lim; Oh Joo Kweon; Yoojeong Choi; Sumi Yoon; Tae-Hyoung Kim; Mi-Kyung Lee (Scientific Reports, 2023)
Abstract We aimed to analyze the kinetics of T-cell-mediated and B-cell-mediated humoral immune responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) before and after booster vaccination, as well as the impacts of the in vitro test results the type of vaccination on the prediction of SARS-CoV-2 infection. A total of 240 healthcare workers vaccinated twice were serially tested using an interferon gamma release assay (IGRA) and a neutralizing antibody (nAb). At the end of the study, we investigated the history of SARS-CoV-2 infection of all the enrolled participants to analyze the effects of the test results and the type of vaccination on SARS-CoV-2 infection. Overall, the positive rates were 52.3% and 80.0% for IGRA and 84.6% and 100% for the nAb test before and after booster vaccination, respectively. However, the positive rates were 52.8% for IGRA and 100% for nAb 3 months after booster vaccination. The in vitro test results and the type of vaccination were not associated with SARS-CoV-2 infection. The antibody response caused by the SARS-CoV-2 vaccination lasted more than 6 months, although the response of the T-cells disappeared rapidly after 3 months. However, these in vitro results and the type of vaccination cannot be used for predicting the risk of SARS-CoV-2 infection.